Cancer phenotype as the outcome of an evolutionary game between normal and malignant cells - Dingli, D. (2017)
This work was supported by Mayo Foundation ( DD), FCT Portugal (FACCC and JMP), FNRS Belgium (FCS) and FWO Belgium (SVS).